Socialization of Deep Learning Approach in the Digital Era for Teachers in Indonesia: Sosialisasi Pendekatan Pembelajaran Mendalam / Deep Learning di Era Digital bagi Guru di Indonesia - Rahayu, Chika; Zakiya, Hanifah; Falamy, Ryna Aulia; Ubaidillah, Muhammad; Prastyo, Yanuar Dwi; Utami, Lintang Fitra; Hardianti, Desrina; Yosilia, Rani (Institut Riset dan Publikasi Indonesia, 2025)
The Deep Learning approach launched by the Ministry of Primary and Secondary Education is an approach that honors and is not a new curriculum outlined in the academic manuscript. However, there is still a lack of understanding about the Deep Learning approach, with some people thinking that Deep Learning is a curriculum, and many teachers still don’t understand how to plan and implement this approach in the classroom. This service in the form of socialization is carried out to provide teachers in Indonesia with an understanding of the implementation of Deep Learning in the digital era. The socialization was conducted online with approximately 800 participants, most teachers from various regions across Indonesia. The steps of the method used in this socialization include planning, the delivery of material, sharing during the Q&A session, and reflection. This socialization helps teachers to get to know and understand Deep Learning. It can be implemented in the classroom, leading to positive changes in the learning process, which improves students’ learning outcomes to achieve the eight graduate profiles. The result of this socialization activity was met with enthusiasm from the participants, as shown by the positive feedback during the event, such as interactive Q&A and responses from the participants, allowing them to mutually enrich each other’s learning, most of whom are teachers.